MASALAH-MASALAH INTERAKSI SOSIAL SISWA DENGAN TEMAN SEBAYA DI SEKOLAH - sartika, widia (Konselor, 2013)
ABSTRACT The reality on the ground revealed there are some teenage students exhibit behavior that can not work well with their peers, and there are some that are not accepted by the group. This study aimed to describe anything any problems experienced by the students to interact, especially in play and learning in schools. This study used a descriptive approach. Stratified sampling technique is random sampling. The study's findings reveal a problem of social interaction in playing covers issues have the same interests and values​​, understand, provide security, and reliable. Then the problem of social interaction in learning covering problem can respect others, accept others, cooperate, and have the attitude to enjoy life with others in learning. Keyword: Problems, social interaction, peers.